Are We Real When We Fake? Attunement to Object Weight in Natural and Pantomimed Grasping Movements - Ansuini, Caterina; Cavallo, Andrea; Campus, Claudio; Quarona, Davide; Koul, Atesh; Becchio, Cristina (Frontiers in Human Neuroscience, 2016)
Behavioural and neuropsychological studies suggest that real actions and pantomimed actions tap, at least in part, different neural systems. Inspired by studies showing weight-attunement in real grasps, here we asked whether (and to what extent) kinematics of pantomimed reach-to-grasp movement can reveal the weight of the pretended target. To address this question, we instructed participants (n =15) either to grasp or pretend to grasp towards two differently weighted objects, i.e., a light object and heavy object. Using linear discriminant analysis, we then proceeded to classify the weight of the target – either real or pretended – on the basis of the recorded movement patterns. Classification analysis revealed that pantomimed reach-to-grasp movements retained information about object weight, although to a lesser extent than real grasp movements. These results are discussed in relation to the mechanisms underlying the control of real and pantomimed grasping movements.